?ELIMINATION OF NATURALLY OCCURRING AFLATOXINS IN COTTONSEED MEAL - AHMAD, MANSOOR A.; SHAMSUDDIN, ZUZZER A.; KHAN, BUTTOL A. (Biological Sciences - PJSIR, 1996)
Ammoniation appears to be one of the most extensively studied and applied chemical methods. The present study was aimed atdetermining optimum time periodrequired atpilot plantscale todetoxify aflatoxins incottonseed mealbyammoniationundersteampressureandelevatedtemperature.Thedetoxification wasachieved upto97% with onepercentammoniaat99± 1°Cunder0.7±0.035bar steampressure.Thequalityandtextureof startingmaterialwas not significantly altered. This study was also aimed to develop a feasible process for detoxification of aflatoxins in cottonseed mealoncommercialscaleinPakistan.